2018
DOI: 10.1007/s00246-018-1971-z
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Utility of Coronary Artery Lack of Tapering and Perivascular Brightness in Incomplete Kawasaki Disease

Abstract: LT and PB are subjective, poorly reproducible features that can be seen in febrile patients without KD and in healthy children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Os autores desse estudo não consideraram a hiperecogenicidade e o afunilamento das coronárias como fatores relevantes, visto que são achados subjetivos, pouco reprodutíveis e podem ser encontrados tanto em doenças febris como em crianças saudáveis. 23 Na fase crônica, um paciente manteve envolvimento do sistema de condução e dilatação do VE e outro ficou com hipertrofia do VE. As repercussões cardíacas a longo prazo na DK estão ainda pouco esclarecidas.…”
Section: Discussionunclassified
“…Os autores desse estudo não consideraram a hiperecogenicidade e o afunilamento das coronárias como fatores relevantes, visto que são achados subjetivos, pouco reprodutíveis e podem ser encontrados tanto em doenças febris como em crianças saudáveis. 23 Na fase crônica, um paciente manteve envolvimento do sistema de condução e dilatação do VE e outro ficou com hipertrofia do VE. As repercussões cardíacas a longo prazo na DK estão ainda pouco esclarecidas.…”
Section: Discussionunclassified
“…This can also mean that both sexes have the same chance of developing echocardiographic findings but boys are more at risk of a poor outcome when an abnormal echocardiographic feature is found [17]. The most common echocardiographic finding was perivascular brightness, which according to other studies is not considered as a proper sign for diagnosis of KD [18]. Aneurysms were discovered in around 35% of the patients with cardiovascular complications and counts as one of the most important cardiac finding in all studies [19].…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, PB was suggested as a useful diagnostic sign of incomplete presentation of KD in the 2004 AHA diagnostic guideline [4]. However, Yu et al [8] did not confirm the utility of PB, and Rabinowitz et al [9] reported similar results. In the present study, among patients with ≤3 d-Features, two patients showed a small aneurysm and 17 patients showed PB.…”
Section: Discussionmentioning
confidence: 99%